Gut microbiome as a novel cardiovascular therapeutic target. (April 2016) - Singh, Vishal; Yeoh, Beng San; Vijay-Kumar, Matam
Highlights: The gut microbiota (GM) plays a key role in host macromolecule metabolism. GM generates both pro-inflammatory and anti-inflammatory metabolites. GM metabolism modulation can alleviate risk factors of cardiovascular disease (CVD). Probiotics and fecal microbiota transplantation have potential to reduce CVD. Abstract : Over the last two decades, our understanding of gut microbiotal composition and its association with intra-intestinal and extra-intestinal diseases including risk factors of cardiovascular disease (CVD) namely metabolic syndrome and atherosclerosis, have been increased exponentially. A pertinent question which often arises in researchers' community is on how to manipulate the gut microbial ecology to 'cure' the cardiovascular risk factors. Accordingly, in this review we summarized the potential strategies, based on our current knowledge on gut microbiota in modulating CVD, how gut microbiota can be therapeutically exploited by targeting their metabolic activity to alleviate the risk factors of CVD.